Practices and perceptions at the COVID‐19 transition in undergraduate animal science courses - Erickson, MaryGrace (Natural Sciences Education, 2021)
The swift transition to remote learning in response to the COVID‐19 pandemic presented substantial challenges for both students and instructors in post‐secondary natural sciences education. To examine teaching practices and student engagement during the emergency remote learning in the Spring 2020 semester, we surveyed 10 instructors and 261 students in an animal and dairy sciences department at a large midwestern university. Instructors reported using a diversity of teaching practices. On average, students perceived high teaching presence and cognitive presence and moderate social presence during emergency remote learning. Student‐reported educational experience differed substantially between courses and explained a significant amount of variance in student engagement and satisfaction outcomes (p < .001). Open‐ended responses revealed beliefs and attributions about remote learning that shaped students’ interpretations of educational experiences. Results support the validity of the Community of Inquiry (CoI) framework for assessing emergency remote learning and suggest future research on modulators of social presence.